2015
DOI: 10.4095/296915
|View full text |Cite
|
Sign up to set email alerts
|

Geology, Montresor River area, Nunavut, parts of NTS 66-H and NTS 66-I

Abstract: The Montresor River area (parts of NTS 66-H/13, 14, 15, 16, and NTS 66-I/1, 2, 3, 4, 5, 6, 7, 8), part of the Rae structural province, is underlain by granitic rocks of Archean (ca. 2.6 Ga) age and the Paleoproterozoic (<2.19 Ga) Montresor group of metasedimentary rocks. Quartzite, dolostone and metapelite of the lower Montresor group are structurally imbricated (D1) with granitic gneisses and metamorphosed to the amphibolite facies. This structural footwall complex is separated from greenschist-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Where available, strike and dip information from Frisch (2000) and Percival et al (2015) was incorporated into the models.…”
Section: Aseg-pesa-aig 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Where available, strike and dip information from Frisch (2000) and Percival et al (2015) was incorporated into the models.…”
Section: Aseg-pesa-aig 2016mentioning
confidence: 99%
“…2.35, 2.0, 1.9 and 1.85 Ga (Figure 1). Initially considered to be a simple syncline (Frisch, 2000), the Montresor belt consists of a footwall complex made up of structurally interleaved (D1) Archean gneiss and quartzite-carbonate units of the lower Montresor group (<2190 Ma), and above a D2 décollement, low-grade sandstone and siltstone of the upper Montresor group (<1940 Ma; Percival et al, 2015), the focus of this study. Heavy-mineral beds in the upper Montresor give rise to magnetic marker units defining two doublyplunging synclines (D3-D4 interference patterns) resembling elliptical bulls-eyes on aeromagnetic maps (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…The lower Montresor group is commonly cut by granodiorite, granite, and pegmatitic dykes (Percival et al, 2015A, C). Previous studies suggested that these higher-grade amphibolite facies rocks belong to the basement Percival et al, 2015A). (Frisch, 2000;Frisch and Patterson, 1983), but recent work has demonstrated that these units are part of the Montresor belt (Percival et al, 2015C).…”
Section: The Canadian Shieldmentioning
confidence: 93%
“…The belt is 73 km long and 8 km wide, extending from the Montresor River in the northeast to the Back River in the southwest (Frisch, 2000). It structurally forms an open synclinal fold with the southeast limb dipping at 30˚ and the northwest limb dipping 40 -70˚, with localized dip up to 80˚ (Percival et al, 2015A). The base of the syncline is prominently visible as a magnetic low in modern aeromagnetic maps (Tshirhart et al, 2015).…”
Section: The Canadian Shieldmentioning
confidence: 99%
See 1 more Smart Citation